2023
DOI: 10.1155/2023/9990933
|View full text |Cite
|
Sign up to set email alerts
|

Usability Evaluation of Dashboards: A Systematic Literature Review of Tools

Abstract: Introduction. In recent years, the use of dashboards in healthcare has been considered an effective approach for the visual presentation of information to support clinical and administrative decisions. Effective and efficient use of dashboards in clinical and managerial processes requires a framework for the design and development of tools based on usability principles. Objectives. The present study is aimed at investigating the existing questionnaires used for the usability evaluation framework of dashboards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…This paper outlines the protocol to explore how different initial key messages impact the level of behavioural engagement with the CARA dashboard. User research can determine a dashboard's overall performance and ensures rigorous design and implementation, assesses usefulness, operability, ease of use, satisfaction, user interface, content, as well as system capabilities [11,34].…”
Section: Discussionmentioning
confidence: 99%
“…This paper outlines the protocol to explore how different initial key messages impact the level of behavioural engagement with the CARA dashboard. User research can determine a dashboard's overall performance and ensures rigorous design and implementation, assesses usefulness, operability, ease of use, satisfaction, user interface, content, as well as system capabilities [11,34].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the qualitative method (think-aloud) and a questionnaire will be used in the dashboard evaluation phase. Generally, questionnaires are the most commonly used tools for usability evaluation due to the simplicity of data analysis (34). However, a combination of qualitative and quantitative approaches is suggested to appropriately measure the usability of technologies (34).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the proliferation of dashboards throughout healthcare, we found major opportunities to improve the development process of dashboards. Half of dashboards (n=59/119, 50.0%) did not involve end users in the development process, and even fewer (26/118, 22.0%) included formative usability testing, which are effective strategies to improve usability and adoption [219,220]. This corroborates the findings a prior systematic review of safety dashboards, which found a minority of dashboards used formative usability testing [221], and another recent scoping review which found that even when completed, usability testing is often incomplete [219].…”
Section: Principal Findings and Comparison With Prior Workmentioning
confidence: 99%